The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/myc.12250
|View full text |Cite
|
Sign up to set email alerts
|

Zygomycetes: an emerging problem in the clinical laboratory

Abstract: This supplement of 'Mycoses' is devoted to infections caused by a group of fungi traditionally known as the zygomycetes. The Zygomycota represent an important group of medically important opportunistic fungi, which cause devastating fungal infections in humans and animals with severe underlying immune or metabolic disorders. These infections are increasing in numbers due to the growing populations of patients with uncontrolled diabetes and immunosuppression, as well as the increased use of prophylactic measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, we recently showed that the early stages of infection control are critical for predicting disease outcome 41 . Consistent with this, the majority of mucormycosis patients have predisposing factors that impact phagocyte recruitment, including iron overload, diabetes mellitus, neutropenia, organ transplantation, trauma, and corticosteroid therapy 19,22,34,42-50 . Outbreaks of R. microsporus in hospitals have been linked to the use of contaminated supplies during treatment of immunocompromised patients 51-55 .…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, we recently showed that the early stages of infection control are critical for predicting disease outcome 41 . Consistent with this, the majority of mucormycosis patients have predisposing factors that impact phagocyte recruitment, including iron overload, diabetes mellitus, neutropenia, organ transplantation, trauma, and corticosteroid therapy 19,22,34,42-50 . Outbreaks of R. microsporus in hospitals have been linked to the use of contaminated supplies during treatment of immunocompromised patients 51-55 .…”
Section: Introductionmentioning
confidence: 56%
“…Pathogenic Mucorales span multiple genera, with the Rhizopus genus causing almost half of all documented cases and high mortality in susceptible patient populations (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic Mucorales span multiple genera, with the Rhizopus genus causing almost half of all documented cases and high mortality in susceptible patient populations. [6][7][8][9][10][11][12][13] Infection occurs through inoculation with dormant, immunologically inert spores. Upon germination, these spores become metabolically active and begin to swell.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of mucormycosis is relatively low, but it constitutes a significant area of concern in immunocompromised patients, including pediatric patients with malignances [ 4 , 5 ]. One of the major problems concerning mucormycosis is the early accurate diagnosis and the identification of the involved organism [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%